2014
DOI: 10.1080/15459624.2014.908259
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Chemical Permeation of Disposable Latex, Nitrile, and Vinyl Gloves Exposed to Simulated Movement

Abstract: Glove movement can affect chemical permeation of organic compounds through polymer glove products. However, conflicting reports make it difficult to compare the effects of movement on chemical permeation through commonly available glove types. This study was aimed to evaluate the effect of movement on chemical permeation of an organic solvent through disposable latex, nitrile, and vinyl gloves. Simulated whole-glove permeation testing was conducted using ethyl alcohol and a previously designed permeation test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
2
24
0
1
Order By: Relevance
“…Involvement of the dorsa of the hands and interdigital webs suggests possible exposure during this process, as patients reported occasional handling without gloves – owing to intolerance to gloves in 2 of our patients. Moreover, thin latex gloves may be permeable to these allergens, as is the case with many small chemicals that induce ACD . Involvement of the forearms and face can be caused by hand transport or contamination of working surfaces, but airborne exposure can also occur .…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the dorsa of the hands and interdigital webs suggests possible exposure during this process, as patients reported occasional handling without gloves – owing to intolerance to gloves in 2 of our patients. Moreover, thin latex gloves may be permeable to these allergens, as is the case with many small chemicals that induce ACD . Involvement of the forearms and face can be caused by hand transport or contamination of working surfaces, but airborne exposure can also occur .…”
Section: Discussionmentioning
confidence: 99%
“…In the 1980 s, healthcare workers dramatically increased the use of latex gloves because of concerns of infectious agents (such as HIV and Hepatitis B viruses) 4) . When compared with synthetic gloves (nitrile and vinyl), latex gloves appear to be stronger, more flexible, and protective 20) , and hence are better acceptable by workers.…”
Section: Application Of Latex In Medical and Food Industriesmentioning
confidence: 99%
“…The results showed that the efficiency of face masks appropriate to reduce exposure to chemicals are inhaled to reach 70% -95%. 20 Disposible latex gloves can inhibit the penetration of chemicals through the skin. 21 .Goggles, protective clothing and shoes can reduce chemical exposure.…”
Section: Resultsmentioning
confidence: 99%